Unplugged Coding to Develop Computational and Collaborative Thinking in Early Childhood Education - Oktaviani, Putri; Diana, Diana; Waluyo, Edi; Formen, Ali (JURNAL PENDIDIKAN USIA DINI, 2025)
Integrating computational and collaborative thinking from early childhood is essential in the digital era. This study examined the implementation of Unplugged Coding computer-free programming at the Larasati Early Childhood Education Cluster, with a focus on children’s cognitive and social development. Using a qualitative case study method, data were collected through observation, interviews, and documentation at TK Islam An-Nur Kedungringin. Activities involved grid floor games, number dice, and directional arrows, with teachers acting as facilitators. Results showed that 87.5% of children demonstrated improvement in computational thinking components such as sequencing, pattern recognition, decomposition, and algorithmic reasoning. Moreover, 81.2% of children exhibited enhanced collaborative skills, including turn-taking, group problem-solving, and active communication. Contributing factors included structured planning, engaging learning tools, and a supportive environment. Limitations involved limited infrastructure and varying teacher readiness. The study concludes that Unplugged Coding is an effective, low-tech approach to foster 21st-century skills in early learners and recommends broader implementation supported by teacher training and curriculum integration.